The future of registered partnerships : family recognition beyond marriage? / edited by Jens M. Scherpe, Andy Hayward. - Scherpe, Jens M., 1971-; Hayward, Andy (European family law series, 2017)
The book is required reading for all concerned with policy in this field academics and all concerned with advising clients about entering or dissolving civil partnerships. It may well be that Justices of the Supreme Court will be reaching for their copies when considering judgement in the Steinfeld case." - Martin Downs (April 2018 Family Law Journal) A book series dedicated to the harmonisation and unification of family and succession law in Europe. The series includes comparative legal studies and materials as well as studies on the effects of international and European law making within the national legal systems in Europe. The books are published in English French or German under the auspices of the Organising Committee of the Commission on European Family Law (CEFL).In many jurisdictions registered partnerships were introduced either as a functional equivalent to marriage for same-sex couples or as an alternative to marriage open to all couples. But now that marriage is opened up to same-sex couples in an increasing number of jurisdictions is there a role and a need for another form of formalised adult relationship besides marriage? In this book leading family law experts from 15 European and non-European countries explore the history and function of registered partnership in their own jurisdictions. Further chapters look at the impact of the European Convention on Human Rights and European Union Law on the regulation of registered partnerships. In the concluding chapters the different approaches are analysed and compared. This book provides the foundation for an informed discussion not only on changes to the implementation of registered partnership schemes but also more generally for reviewing the law concerning the recognition of adult relationships. About the editors: Dr Dr Jens M. Scherpe is a Reader at the University of Cambridge and Cheng Yu Tung Visiting Professor at the University of Hong Kong Dr Andy Hayward is a Lecturer in Family Law at Durham Law School Durham University.